2001
DOI: 10.1093/brain/124.7.1290
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathology of inflicted head injury in children: I. Patterns of brain damage

Abstract: Fifty-three cases of non-accidental head injury in children were subjected to detailed neuropathological study, which included immunocytochemistry for microscopic damage. Clinical details were available for all the cases. There were 37 infants, age at head injury ranging from 20 days to 9 months, and 16 children (range 13 months to 8 years). The most common injuries were skull fractures (36% of cases), acute subdural bleeding (72%) and retinal haemorrhages (71%); the most usual cause of death was raised intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
191
2
20

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(227 citation statements)
references
References 29 publications
14
191
2
20
Order By: Relevance
“…1,2,5,15) Cerebral hypoxia/ischemia in SBS may be explained by numerous factors, such as reactive vasospasm adjacent to hemorrhagic lesions, strangulation, cervicomedullary injuries, and persistent crying and apnea. 8,9) Diffusion-weighted MR imaging in our case showed no obvious ischemic lesions. We assumed that the delay between examinations (16 months from the first hospitalization) may have masked any injury.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…1,2,5,15) Cerebral hypoxia/ischemia in SBS may be explained by numerous factors, such as reactive vasospasm adjacent to hemorrhagic lesions, strangulation, cervicomedullary injuries, and persistent crying and apnea. 8,9) Diffusion-weighted MR imaging in our case showed no obvious ischemic lesions. We assumed that the delay between examinations (16 months from the first hospitalization) may have masked any injury.…”
Section: Discussionmentioning
confidence: 43%
“…7) Shaken baby syndrome (SBS) is a form of abuse that can cause severe injuries such as subdural hematoma (SDH), subarachnoid hemorrhage, hemorrhagic contusion, and/or diffuse axonal injury. 8,12,13) We describe a case of SBS manifesting as chronic SDH detected by magnetic resonance (MR) imaging, diffusionweighted MR imaging, and single photon emission computed tomography (SPECT).…”
Section: Introductionmentioning
confidence: 99%
“…2 The relationship between infantile SDH and trauma has been challenged in recent years. One series of neuropathological postmortem studies [3][4][5] concluded by speculating that in a susceptible infant, "subdural and retinal bleeding might result from any event that initiated apnoea or significant hypoxia, with brain swelling." 5 Thus, in some infants with unexplained SDH a presumptive diagnosis of AHT might be incorrect.…”
Section: Resultsmentioning
confidence: 99%
“…Geddes first suggested that the majority of diffuse axonal injuries in fatal cases of AHT are ischemic rather than traumatic based on beta-amyloid precursor protein (BAPP) staining patterns, traumatic axonal injuries being restricted to the cervicomedullary junction and upper spinal cord. 12 A number of other small case series have documented upper cervical spinal cord injuries in fatal cases of AHT. 15,20,26 In the largest study to date, Brennan and colleagues documented cervicomedullary and/or upper spinal cord injuries in 29 (71%) of 41 fatal cases of AHT.…”
Section: Contribution Of Neuroimaging To Timing Of Ahtmentioning
confidence: 99%